CERTYFIKACJA KOMPETENCJI JĘZYKOWYCH A ROZWÓJ ZAWODOWY ŻOŁNIERZY W POLSKICH SZKOŁACH WOJSKOWYCH - Iwanowska, Anna (Neofilolog, 2019)
At present, soldiers who want to serve abroad have to achieve a specific level of language proficiency both in its general and professional variety. To prove their competences, they have to take examinations compatible with STANAG 6001 standards. The purpose of this article is to present the impact of formal assessment on soldiers’ professional development in Polish military schools and the factors which are crucial to soldiers’ successful language learning.